2001
DOI: 10.1021/jf000537w
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Hydroxytyrosol Acetate Compared with That of Other Olive Oil Polyphenols

Abstract: Hydroxytyrosol acetate was synthesized, and the antioxidant activity of this olive oil component was assessed in comparison with that of other olive oil components, namely hydroxytyrosol, oleuropein, 3,4-DHPEA-EA, and alpha-tocopherol in bulk oil and oil-in-water emulsions. The activity of the compounds was also assessed by scavenging of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals. Hydroxytyrosol acetate had a weaker DPPH radical scavenging activity than hydroxytyrosol, oleuropein, or 3,4-DHPEA-EA but it had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
227
3
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(261 citation statements)
references
References 21 publications
17
227
3
14
Order By: Relevance
“…Both compounds also scavenged hydroxyl radicals, but in this case oleuropein showed greater activity [114]. Gordon et al [115] investigated the antioxidant activity of hydroxytyrosol acetate by scavenging of DPPH radicals in comparison with that of the phenolic extract from VOO and the pure components hydroxytyrosol, oleuropein, 3,4-DHPEA-EA, and α-tocopherol in bulk oil and oil-in-water emulsions. In this study the authors showed that hydroxytyrosol acetate had a weaker DPPH radical scavenging activity than hydroxytyrosol and 3,4-DHPEA-EA was slightly less effective than hydroxytyrosol acetate in oil but was the most effective hydroxytyrosol derivative in an emulsion oil in water.…”
Section: Phenols As Related To Oxidative Stability Of Voomentioning
confidence: 99%
“…Both compounds also scavenged hydroxyl radicals, but in this case oleuropein showed greater activity [114]. Gordon et al [115] investigated the antioxidant activity of hydroxytyrosol acetate by scavenging of DPPH radicals in comparison with that of the phenolic extract from VOO and the pure components hydroxytyrosol, oleuropein, 3,4-DHPEA-EA, and α-tocopherol in bulk oil and oil-in-water emulsions. In this study the authors showed that hydroxytyrosol acetate had a weaker DPPH radical scavenging activity than hydroxytyrosol and 3,4-DHPEA-EA was slightly less effective than hydroxytyrosol acetate in oil but was the most effective hydroxytyrosol derivative in an emulsion oil in water.…”
Section: Phenols As Related To Oxidative Stability Of Voomentioning
confidence: 99%
“…For example, the hydrolyzing metabolites of 117 and 121, such as hydroxytyrosol (HT) and 3-hydroxyphenylpropionic acid (3-HPP), possessed antioxidant [116,117], neuroprotective [118][119][120], and anti-inflammatory activities [121,122]. Identification of 117's metabolites produced by human intestinal bacteria, biliary metabolites as well as urinary and fecal ones was reported.…”
Section: Pharmacokinetics Of Echinacoside (117) and Acteoside (121)mentioning
confidence: 99%
“…Papers concerning the analysis of the phenolic components of the olive fruits, olive oil [8,9] and olive leaves [10][11][12][13][14] are can be found in the literature, but the investigation of those volatiles is mostly correlated to their antioxidant properties. The reports describing antimicrobial properties of phenolic compounds in olive products refer to compounds obtained from olive fruit, particularly hydroxytyrosol and oleuropein [15,16].…”
Section: Introductionmentioning
confidence: 99%